Hubungan Karakteristik dan Kebiasaan Menyikat Gigi dengan Kejadian Abrasi Gigi Pada Pegawai Yayasan Masjid Al-Ikhlas Cilandak Jakarta - Ngatemi; Erna Sariana (UHAMKA Press, 2019)
ABSTRACT Abrasion is damage to dental tissue due to foreign objects, such as toothbrushes and toothpastes that contain abrasive ingredients. Abrasion caused by brushing teeth in a horizontal direction and with excessive emphasis. This study aims to obtain an overview of the relationship between the characteristics and habits of brushing teeth with the incidence of dental abrasion in employees of the Al-Ikhlas Masjid Cilandak Foundation in Jakarta. This research is a descriptive study with a cross sectional design. The research sample used total sampling totaling 32 employees of Masjid Al-Ikhlas Foundation. Data collection through direct interviews and observations by filling out checklist sheets and dental abnormalities (tooth abrasion) cards. Data analysis was conducted in univariate and bivariate. The results of univariate analysis showed that the incidence of tooth abrasion was mostly in the high category (53.1%), employee age> 38 years (56.3%), female sex (56.3%), tooth brushing frequency <3 times (62, 5%), and the tooth brushing technique is mostly good (56.3%). The results of bivariate analysis, variables that were significantly associated with dental abrasion events were the frequency of tooth brushing (p = 0.035 and OR = 7,000), and tooth brushing techniques (p = 0.029 and OR = 7.333). Keywords: Dental abrasion, characteristics, and habit of brushing teeth